2008
DOI: 10.1002/j.2050-0416.2008.tb00770.x
|View full text |Cite
|
Sign up to set email alerts
|

Arsenic, Cadmium and Lead in Beers from the Italian Market

Abstract: Nineteen beer brands from the Italian market were surveyed for the presence of arsenic, cadmium and lead in January of 2007. Detection was performed by means of inductively coupled plasma‐mass spectrometry (ICP‐MS). Average arsenic content was 10.82±5.54 μg/L, while cadmium (0.16±0.15 μg/L) and lead (1.84±3.24 μg/L) were significantly lower (P<0.05). Overall, this survey indicated that beer may contribute heavy metals to the diet. Nevertheless, the dietary exposure to these contaminants is unlikely to constitu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
32
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 36 publications
5
32
0
Order By: Relevance
“…The levels of Cu obtained in this work are in agreement with that of other studies in Nigeria [22], Brazil [24] and Norway [25]. The lead level observed in this study is in line with that of other surveys [5,22,24]. For Mn the results obtained in this work are comparable to the levels reported in beers from Poland [26], Brazil [24] and Norway [25].…”
Section: Comparison Of the Metal Levels In Beer Samples With Reportedsupporting
confidence: 92%
See 3 more Smart Citations
“…The levels of Cu obtained in this work are in agreement with that of other studies in Nigeria [22], Brazil [24] and Norway [25]. The lead level observed in this study is in line with that of other surveys [5,22,24]. For Mn the results obtained in this work are comparable to the levels reported in beers from Poland [26], Brazil [24] and Norway [25].…”
Section: Comparison Of the Metal Levels In Beer Samples With Reportedsupporting
confidence: 92%
“…The concentration of Cd in the present study is comparable to the levels reported in beers available in Nigeria [22], Italy [5] and Brazil [23]. The levels of Cu obtained in this work are in agreement with that of other studies in Nigeria [22], Brazil [24] and Norway [25].…”
Section: Comparison Of the Metal Levels In Beer Samples With Reportedsupporting
confidence: 92%
See 2 more Smart Citations
“…The mixture was heated for 1 h (100°C) until complete clarification. The sample was allowed to cool to room temperature, filtered and diluted to 25 mL with ultra pure water 5 . Analytical blanks were prepared in a similar manner, but omitting the test sample.…”
Section: Methodsmentioning
confidence: 99%